Concept of Transitory Alienations in Legal Matters - Avendaño Hübner, Jorge (1986)
The paper examines the concept of “transitory alienations” from a legal and medical perspective, focusing on how certain temporary alterations of consciousness affect imputability in legal cases. To that extent, the text begins by explaining that disorders such as epilepsy, sleepwalking, drunkenness and violent emotion can lead to states of temporary unconsciousness. Particularly, in the case of epilepsy, its manifestation is detailed in variants such as grand mal, petit mal and psychomotor epilepsy, each with specific symptoms that alter the behavior and consciousness of those affected, causing them to commit violent acts without awareness of the act. Next, imputability in law is analyzed, emphasizing that a person's capacity to understand or intend his or her acts is fundamental for criminal liability. Finally, the author highlights that in several legal systems, exoneration or mitigation of punishment is allowed for persons in states of temporary unconsciousness, as long as there is an exhaustive medical and legal evaluation that justifies the mental state of the accused at the time of the crime.